Treatment of colorectal cancer by anticancer and antibacterial effects of hemiprotonic phenanthroline-phenanthroline+ with nanomicelle delivery - Yingying Zhang; Zizhen Zhao; Jingli Li; Qinghua Wang; Zhigang Fan; Zhibo Yuan; Yixiao Feng; Ailing Fu (Asian Journal of Pharmaceutical Sciences, 2023)
Colorectal cancer (CRC) is a common digestive tract tumor worldwide. Specific microorganisms, including Fusobacterium nucleatum (F. nucleatum) and Escherichia coli (E. coli), are abundant in colonic mucosa and can promote the cancer progression and malignancy. Therefore, a therapeutic strategy is proposed to deliver effective drugs to colorectum for both anticancer and antibacteria. Here we used thin-film dispersion method to encapsulate hemiprotonic phenanthroline-phenanthroline+ (ph-ph+) into nanomicelle. The results showed that the drug-loading nanomicelle had good dispersion, and the particle size was about 28 nm. In vitro assay indicated that the nanomicelle was active against CRC-related obligate and facultative anaerobes. In human CRC cells, the nanomicelle could effectively inhibit cell proliferation and induce apoptosis. In vivo distribution showed that the nanomicelle could release ph-ph+ mainly in the colorectum. In CRC model mice, the nanomicelle significantly reduced tumor number and volume, and decreased the bacteria load and colorectal inflammation. Together, the study identifies that the ph-ph+nanomicelle has the potential to apply in treating CRC, and also suggests that anticancer combined with antimicrobial therapy would be a feasible way for CRC therapy.